Digital Tourism In ASEAN During Covid-19 Pandemic - Salam, Usmar (LP2M, 2023)
The tourism industry's landscape has been heavily impacted by the development of digitalization. This scope has specifically affected how the utilization of technology has somewhat influenced the existence of a digitally driven market, to which those industries must adapt in these new environments. Ever since its implementation through online travel agencies, which has further exacerbated the trend toward entirely new virtual experiences, along with various digital marketing efforts. As such, the advantages of digital tourism resonate in economic development, enhanced branding, and increased resistance against future pandemics such as COVID-19, as shown in the article through several case studies. Countries like Indonesia, Malaysia, and Thailand are slowly striving to expand and rejuvenate their tourism sector through the pathway of digital tourism. This article perceptively showcases how the importance of digitalization is transforming global tourism industries in Southeast Asia. Through digital tourism, a plausible way has been paved for governments to approach new markets and reach new levels of competitiveness, thereby elevating their status to attract travelers. This path is also harnessed by businesses at all kinds of levels, as it inclusively provides possibilities to access the digital world. Therefore, under the adoption of digital tourism strategies, nations can address not only immediate challenges but also position themselves to gradually transition towards sustainable tourism growth in the post-pandemic era.